Pengembangan Media Pembelajaran Pop-Up Book pada Materi Struktur Atom - Fazrul Aprilyani; Masriani Masriani; Lukman Hadi (Jurnal Ilmiah Ar-Razi, 2021)
This study aims to determine the feasibility of Pop-Up Book Media on Atomic Structure Material which was developed based on the results of expert tests (expert judgment). The form of this research is research and development (R&D) which adopts the Suyanto and Sartinem development model. The subject of this research is Pop-Up Book Media on Atomic Structure Material. The data collection technique uses indirect communication techniques. The assessment instrument used is in the form of a feasibility questionnaire. Media Pop-Up Book on Atomic Structure Material was validated by each of 3 experts in every aspect, namely, aspects of the feasibility of content, presentation, language and graphics. The results of data analysis show that the Pop-Up Book Media on the Atomic Structure Material developed is very suitable for use in learning in terms of content feasibility with a percentage of 85%, 88% presentation, 85.71% language, and 87.45% graphics with very high criteria.